Injury incidence and prevalence in elite short-course triathletes: a 4-year prospective study - Crunkhorn, M. L.; Toohey, L. A.; Charlton, P.; Drew, M.; Watson, K.; Etxebarria, N. (British Journal of Sports Medicine, 2024)
Objective To characterise the prevalence, incidence rate (IR) and burden of injuries in elite short-course triathletes over a 4-year training and competition period.